FRAMING POWER AND IDEOLOGY IN PRABOWO SUBIANTO'S PRESIDENTIAL SPEECH - Nasrullah, Riki; Budiman, Arip; Prayogi, Arditya; Yuliyanto, Andik; Parmin, Parmin; Isam, Hishamudin (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
Political speeches function not only as formal addresses but also as powerful tools for constructing ideological narratives, legitimizing authority, and influencing public opinion. In a politically polarized and socially diverse country like Indonesia, presidential discourse plays a crucial role in uniting disparate groups and articulating visions for national development and reform. This study critically examines how President Prabowo Subianto frames power and ideology in his 2024 inaugural presidential speech by investigating the linguistic strategies and discursive mechanisms used to construct an image of inclusive leadership, address systemic corruption, and reinforce national identity. Employing a qualitative approach grounded in Critical Discourse Analysis (CDA), the research integrates van Dijk’s theory of power and ideology, Fairclough’s modality theory, Wodak’s critical pragmatics, Lakoff and Johnson's conceptual metaphor theory, and Moscovici's theory of social representation. The primary data consists of the official transcript of Prabowo's speech, retrieved from government sources and analyzed through purposive sampling to identify ideologically salient segments. These were manually coded for modality, speech acts, metaphorical constructions, and group representations. The analysis reveals that Prabowo constructs an assertive yet inclusive leadership persona by using a high-certainty modality to project confidence in achieving national goals, particularly food and energy self-sufficiency. Deontic expressions frame these goals as collective moral obligations. Assertive and commissive speech acts function to inform and mobilize, reinforcing his credibility and political commitment. Conceptual metaphors such as